2009
DOI: 10.1002/app.30755
|View full text |Cite
|
Sign up to set email alerts
|

Development of low‐biofouling polypropylene feedspacers for reverse osmosis

Abstract: Microbial fouling, or biofouling, is the accumulation of microorganisms onto material surfaces. The goal of this project was to develop low-biofouling polypropylene (PP) films through the functionalization of PP by a spacer arm with metal chelating ligands charged with copper ions. Virgin and modified PP films were put in contact with 3.0 Â105 Escherichia coli cells/mL solutions for periods of time varying from 24 to 168 h. Fourier transform infrared spectroscopy (FTIR) and x-ray energy dispersive spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…The results of these experiments observed lower rates of flux decline and no significant copper leaching from the feed spacers [19]. The study also observed that modified PP feed spacers had increased the membrane resistance to fouling and biofouling compared to unmodified feed spacers [19], and could potentially increase the performance and longevity while decreasing the operating cost [18]. Since the work presented here was on material development, samples were too small for studies longer than 24-60 h.…”
Section: Filtration Experimentsmentioning
confidence: 86%
See 2 more Smart Citations
“…The results of these experiments observed lower rates of flux decline and no significant copper leaching from the feed spacers [19]. The study also observed that modified PP feed spacers had increased the membrane resistance to fouling and biofouling compared to unmodified feed spacers [19], and could potentially increase the performance and longevity while decreasing the operating cost [18]. Since the work presented here was on material development, samples were too small for studies longer than 24-60 h.…”
Section: Filtration Experimentsmentioning
confidence: 86%
“…1. Chelate groups are strong Lewis acids, which can form coordinate bonds with the metal ion by sharing three or more pairs of electrons and a polymer ligand must donate unshared electrons to the metal ion to form metalligand bonds [18]. In the group of multidentate ligands, iminodiacetic acid (IDA) holds an aminopolycarboxylate, which offers a secondary amine hydrogen to react with alternate functional groups [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the multidentate ligands, iminodiacetic acid (IDA) possesses one aminopolycarboxylate and provides a reactive secondary amine hydrogen to react with alternate functional groups [4]. Hence, IDA can be more easily introduced to the side chair of a polymer or vinyl monomer via an epoxy group reaction of glycidyl methacrylate (GMA) and IDA [5]. This reaction has two advantages, (1) GMA is a commercial industrial material that is cheaper than any other vinyl monomers that possess an epoxy ring in the side chain; and (2) it produces a vinyl monomer that can be polymerized in the presence of an initiator and can be grafted to activated polymer surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this project was to functionalize PP with copper (Cu) [5] and to demonstrate that Cu-charged PP could be used to make low-biofouling feedspacers for spiral wound elements. In previous proof-of-concept investigations, PP was functionalized using a spacer arm (GMA) and metal chelating ligands (IDA) to which copper was chelated [5].…”
Section: Introductionmentioning
confidence: 99%